Internet of Things : A Way of Transforming Conventional Agriculture - P. N. Patel; Meera Padaliya; Sanjay VC; Basu Anand (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The Internet of Things (IoT) is the network of various devices seamlessly exchanging data. IoT has initiated the 4th agricultural revolution known as Agriculture 4.0/Digital Agriculture (DA)/Precision Agriculture (PA)/Smart Agriculture (SA). All farming activities can be monitored and managed remotely. With IoT, agriculture is becoming more energy-efficient, precise and effective. IoT is emerging as a potential solution to current world problems. In this review paper, the application of IoT in various agricultural activities is discussed. The paper highlights how IoT is transforming the execution of various agricultural activities.